Carboranes as Aryl Mimetics in Catalysis: A Highly Active Zwitterionic NHC‐Precatalyst. Issue 33 (10th April 2017) - Selg, Christoph; Neumann, Wilma; Lönnecke, Peter; Hey‐Hawkins, Evamarie; Zeitler, Kirsten
Abstract: Modern catalysis takes advantage of aryl‐based interactions to tune and control reactions. In the design of N ‐heterocyclic‐carbene catalysts, both the electronic and steric nature of the nitrogen substituents play a crucial role. Although hydrocarbon‐based systems and especially aryl residues have contributed considerably to overcome multifaceted catalytic challenges, the unique properties of carborane moieties, including delocalized charge, potential planar chirality, and well‐known thermodynamic stability, offer unprecedented opportunities to develop new catalysts while being employed as aryl mimetics. We report a straightforward synthetic route to a novel zwitterionic triazolium‐based N ‐heterocyclic carbene (NHC) precatalyst bearing a 7, 8‐dicarba‐ nido ‐undecaboranyl substituent. The catalyst's excellent activity and its broad applicability are demonstrated in a wide range of organocatalytic transformations. Comparison of the performance with known N ‐aryl NHC catalysts offers preliminary insights into the stereoelectronic nature of this nido ‐carboranyl substituent. Abstract : Catalyst's first steps : The first N ‐carboranyl‐substituted zwitterionic triazolium NHC‐precatalyst for covalent organocatalysis is presented. Its broad applicability and reactivity profile are examined in a wide range of test reactions. Presentation and discussion of the unique spectroscopic and crystallographic properties pave the way for versatile applications of this novel class of catalysts, which are bench‐stable and easily accessible.